Ground Truth Soil Moisture Estimation Along With Minimal Drizzling Time - Vivek Chamoli, Rishi Prakash, Anurag Vidyarthi, Shivangi Barthwal (International Journal of Modern Agriculture, 2021)
The aim of this study was to determine the soil moisture along with minimal drizzling time using two methods using hot air convection oven (HA-CO) and microwave oven (MO) to find out the best method for estimation the soil moisture. The convection oven method was considered as the most accurate method to determine the soil moisture; hence, we utilized this method as source for assessing the results. The experiment was conducted in lab which was completely based on random 110 dry soil samples weight of approximately 100 gram from the bare land. In convection oven method we used 105 Â°C for 24 hours and in microwave oven method we used different thermal power (180, 360, 540, 720 and 900 watt) for different time duration. The result based on the RMSE between soil moisture retrieval from hot air convection oven method and soil moisture retrieval from microwave oven method. 720 watt takes 15 minutes to dry the soil while 900 watt takes 8 minutes; both are gives approximately same results as convection oven method, which takes 24 Hours. Therefore for retrieval of soil moisture we can utilize the microwave oven method at 900 watt power. The low RMSE for 900 watt is 0.51% shows that the microwave oven method is most convenient, time saving and safe method for retrieval of soil moisture.